Supplementary protection certificates and their impact on access to medicines in Europe: case studies of sofosbuvir, trastuzumab and imatinib - Yuanqiong Hu; Dimitri Eynikel; Pascale Boulet; Gaelle Krikorian (Taylor & Francis Group, 2020)
In recent years, there has been increasing pressure on public health systems in high-income countries due to high medicines prices, one of the underlying causes of which are the market monopolies granted to pharmaceutical undertakings. These monopolies have been facilitated by expanded forms of intellectual property protections, including the extension of the exclusivity period after the expiration of the patent term concerning medicinal products. In the European Union such an approach lies in the Supplementary Protection Certificate, a mechanism formally introduced under Regulation 1768/92/EEC (now: Regulation 469/2009/EC, amended). After more than 20 years of implementation since it was first introduced, the common justifications for SPCs are being challenged by recent findings as to their functioning and impact. Similarly, legitimate questions have been voiced as to the negative impact of SPCs on timely access to affordable medicines. On the basis of an analysis of three medicines for hepatitis C and cancer treatments, the present article critically engages with the policy justifications underlying SPCs. It then analyses access challenges to a hepatitis C medicine and an HIV treatment in Europe, highlighting the social cost of the introduction of SPCs. Both the normative and empirical analyses have demonstrated that the common justifications supporting the SPC regime are deeply questionable. The addition of SPC exclusivity has also heavily delayed competition and maintained high medicines prices in European countries. Ultimately, the granting of such extended exclusive private rights on medicines may result in unnecessary suffering and be a factor in the erosion of access to medicines for all.